Simple Apparatus for Adding Small Amounts of Powder Materials under an Inert Atmosphere - Karak, Milandip; Joh, Yohei; Khodjaniyazov, Khamid U.; Sagdullaev, Shamansur S.; Oishi, Tohru; Torikai, Kohei (Synlett, 2019)
Addition of reactants under an inert atmosphere is a fundamental but extremely important technique in synthetic chemistry. Although this is achievable in many cases by using a glove box or a Schlenk-and-syringe technique, the direct addition of powder (solid) materials without contamination by air or moisture has been difficult, especially in the later stages of a reaction. Here, we offer a simple and small apparatus to realize powder addition with easy handling. Use of this apparatus permitted one-pot glycosylation reactions that required extremely dry conditions to be performed in a highly reproducible manner.
Keywords: apparatus; powder handling; glycosylation; inert atmosphere; moisture sensitivity